Designing Semester Insturctional Plan of Reading Course at English Education Department - Septiana, Tri Ilma (Educativo: Jurnal Pendidikan, 2023)
This study to design Semester Instructional Plan and instructional materials of reading courses for English Education Department (further glossed by EED), UIN Sultan Maulana Hasanuddin Banten. To design good Semester Instructional Plan and develop reading materials, this study used Research and Development method by utilizing ADDIE Model. Meanwhile, to gather data this study was used a variety of instruments such as distributed questionnaire to students, conducted interviews, analyzed curriculum document of EED, did consultation to curriculum experts and literacy practitioners. In terms of developing Semester Instructional Plan and instructional materials, this study also referred to manual guideline of developing curriculum from RISTEKDIKTI and learning outcomes in Indonesia Nasional Qualification Framework. The results of this study reveal that in designing Semester Instructional Plan of reading courses, the lecturer must determine learning outcomes which refer to the regulations in National Standard of Higher Education. Moreover, reading strategies and instructional materials at each reading course should be arranged gradually by paying attention to students’ language development and thinking level in order students acquire some reading skills and facilitate them to be skilled readers.